Under the mango tree: A short narrative film on assessing generation Z’s usage of online dating apps and ghosting as a relationship dissolution strategy - Arevalo, Monique A. (Animo Repository, 2022)
Online dating has been prevalent since the conception of dating apps in the 1990s and has been widely accepted as a modern way of seeking romantic relationships. As such, this has also given rise to the practice of ghosting prevalent with the advancement of technology and the advent of social media. This paper explored the concept and background of online dating and dating app usage among Generation Z, along with the process and factors attributed to ghosting in terminating relationships. Essentially, this paper incorporated one Philippine mythological creature, the Kapre, known to possess lustful desires, to offer a more dynamic and local approach to comprehending and depicting the transient nature and misrepresented identities prevalent in the online dating sphere as well as ghosting by employing the forbidden love narrative, primarily between an otherworldly being and a mortal. Furthermore, this paper also locally contextualized online dating in the COVID-19 pandemic setup and ghosting through the Philippine cultural values of hiya and pakikiramdam. Drawing on collected data concerning online dating motivations and gratifications, as well as factors and perceptions of ghosting, supplemented with pertinent discussions on Philippine Mythology, specifically the Kapre, the researchers produced a 16-minute short feature film executed through mobile filmmaking. The film is accompanied by a production book that details the conceptualization process.